2019
DOI: 10.1039/c8nr08224c
|View full text |Cite
|
Sign up to set email alerts
|

Gallium, neon and helium focused ion beam milling of thin films demonstrated for polymeric materials: study of implantation artifacts

Abstract: The focused helium ion beam is ideally suited to precision milling of thin films avoiding implantation artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…This effect was attributed to ion-induced scission of the polymer chains and subsequent cross-linking and compaction, which can be understood in terms of the dominance of energy losses by electronic scattering in the case of light ions such as helium, compared with the nuclear scattering that dominates energy loss for heavier ions. Yet, even in polymeric materials, swelling under implantation with high doses can still occur, and in general, the above studies underscore the advantage for many nanofabrication applications of a sample that is thinner than the ion stopping distance such that implantation effects can be avoided [ 93 ]. Although in some cases subsurface swelling is specifically desired, as described further below.…”
Section: Reviewmentioning
confidence: 99%
“…This effect was attributed to ion-induced scission of the polymer chains and subsequent cross-linking and compaction, which can be understood in terms of the dominance of energy losses by electronic scattering in the case of light ions such as helium, compared with the nuclear scattering that dominates energy loss for heavier ions. Yet, even in polymeric materials, swelling under implantation with high doses can still occur, and in general, the above studies underscore the advantage for many nanofabrication applications of a sample that is thinner than the ion stopping distance such that implantation effects can be avoided [ 93 ]. Although in some cases subsurface swelling is specifically desired, as described further below.…”
Section: Reviewmentioning
confidence: 99%
“…Removal of material by ion milling can lead to several ion irradiation effects on the material, which might change the microstructures and consequently the mechanical properties of samples [ 9 , 13 , 14 , 15 , 16 , 17 , 18 ]. Studies were mainly conducted on metallic and semiconductor materials, and have revealed that Ga + ion implantation occurs in depth of up to several tens of nanometers, depending on the kinetic energy of the beam (acceleration voltage) and the incidence angle of the used ions, and on the milling geometry [ 16 , 19 , 20 , 21 , 22 ]. The main implication is defects at the layer adjacent to the milled surface, including dislocations, amorphization, and intermetallic formation [ 16 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In polymeric materials, the ion irradiation damage is even more severe. It has been shown that the Ga + ions are implanted even deeper into the material, since carbon atoms are lighter [ 22 , 24 ]. There are also local thermal effects, which can cause degradation of the polymer or rapid melting of the material [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source producing the smallest spot size for applications requiring the highest resolution is the atomically sharp Gas Field Ionization Source (GFIS), first developed as the Helium Ion Microscope and then extended to operate with neon [2]. Neon FIB takes advantage of the greater mass of neon versus helium to enable sputtering at a faster rate, while retaining the resolution advantage of a beam formed from ionization events at a single atom -as well as the advantage that the neon beam is chemically inert [3].…”
mentioning
confidence: 99%